Optical Solitary Wave Solutions for the Conformable Perturbed Nonlinear Schrodinger Equation with Power Law Nonlinearity - İnç, Mustafa; Yusuf, Abdullahi; Aliyu, Aliyu Isa; Gulsen, Selahattin; Baleanu, Dumitru (Amer Scientific Publishers, 2018)
In this study, we apply three integration schemes to extract optical soliton solutions for the conformable perturbed nonlinear Schrodinger equation (CPNLSE) with power law nonlinearity (PLN). The integration schemes that are used to carry out such solutions are Sine-Cosine (SC), generalized tanh (GT), and Ricatti-Bernoulli (RB) sub-ODE methods. The constraints conditions for the existence of the solutions are reported. The solutions are obtained using newly proposed fractional derivative called conformable derivative. Numerical simulations of some of the obtained solutions are also illustrated.
Keywords: CPNLSE; SC Methods; GT Method; RB Sub-ODE Method; Conformable Derivative